Investigating the Relationship Between Guilt and Shame Proneness and Moral Injury in Veterans That Have Experienced Active Deployment. (2nd January 2019) - Aldridge, Vicky; Scott, Helen; Paskell, Rachel
Abstract: Moral injury accounts for the complexity of symptoms evident in military personnel which go beyond the posttraumatic stress disorder (PTSD) diagnosis. This study sought to investigate the relationship between guilt and shame proneness and exposure to morally injurious events in a sample of British military veterans ( n  = 104). Participants were recruited through a social media site and completed an online battery of self-report measures. Participants were male ( n  = 99) and female ( n  = 5) with a mean age of 47 years. Fifty-one percent of participants achieved scores on a measure of PTSD that would indicate a probable PTSD diagnosis. Results yielded no significant relationship between guilt and shame proneness and exposure to morally injurious events. There was however a significant relationship between PTSD and morally injurious events, accounting for 43% of the variance, with a medium effect size. When working with veterans with PTSD, clinicians need to be assessing for exposure to morally injurious events to tailor interventions successfully. Future research should look to establish an evidence base for psychological interventions for those that have experienced morally injurious events. Closer consideration of contributing factors, such as type of trauma and historical trauma is also needed to develop the construct further.